Russian painting - Leek, Peter (Temporis collection., 2012)
From the 18th century to the 20th, this book gives a panorama of Russian painting not equalled anywhere else. Russian culture developed in contact with the wider European influence, but retained strong native intonations. It is a culture between East and West, and both influences in together. The book begins with Icons, and it is precisely Icon-painting which gave Russian artist their peculiar preoccupation with ethical questions and a certain kind of palette. It goes on the expound the duality of their art, and point out the originality of their contribution to world art. The illustrations co.